Footwear affects conventional and Sumo deadlift performance - Valenzuela, K. A.; Walters, K. A.; Avila, E. L.; Camacho, A. S.; Alvarado, F.; Bennett, H. J. (Sports, 2021)
Barefoot weightlifting has become a popular training modality in recent years due to anecdotal suggestions of improved performance. However, research to support these anecdotal claims is limited. Therefore, the purpose of this study was to assess the differences between the conventional deadlift (CD) and the sumo deadlift (SD) in barefoot and shod conditions. On day one, one-repetition maximums (1 RM) were assessed for thirty subjects in both the CD and SD styles. At least 72 h later, subjects returned to perform five repetitions in four different conditions (barefoot and shod for both CD and SD) at 70% 1 RM. A 2 × 2 (footwear × lifting style) MANOVA was used to assess differences between peak vertical ground reaction force (VGRF), total mechanical work (WORK), barbell vertical displacement (DISP), peak vertical velocity (PV) and lift time (TIME) during the concentric phase. The CD displayed significant increases in VGRF, DISP, WORK, and TIME over the SD. The shod condition displayed increased WORK, DISP, and TIME compared to the barefoot condition. This study suggests that lifting barefoot does not improve performance as no differences in VGRF or PV were evident. The presence of a shoe does appear to increase the DISP and WORK required to complete the lift, suggesting an increased work load is present while wearing shoes.